2018
DOI: 10.1111/cpr.12463
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Cripto in GRP78 overexpressed human MSCs enhances stem cell viability and angiogenesis during human MSC transplantation therapy

Abstract: These results demonstrate supporting evidences that GRP78-Cripto combination technique offers novel strategy to enhance MSC proliferation, migration and invasion potentials as well as angiogenesis around ischaemic site, ultimately facilitating MSC-based transplantation therapy in ischaemic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…By using the Target Scan Human 7.2 database, we predicted that miR-138-1-3p targets CRIPTO as a downstream molecule, which was confirmed via the luciferase reporter assay and western blotting experiments, demonstrating that miR-138-1-3p can regulate the expression levels of CRIPTO. Several studies have shown that CRIPTO and GRP78 can form a complex on the cell membrane and activate the JAK2/STAT3 pathway, imparting stem cell like characteristics in the host cell with increased proliferation activity (18,31). Our immunohistochemical analysis revealed the colocalization of CRIPTO and GRP78 on the cell membrane that changed when miR-138-1-3p expression was altered.…”
Section: Discussionmentioning
confidence: 62%
“…By using the Target Scan Human 7.2 database, we predicted that miR-138-1-3p targets CRIPTO as a downstream molecule, which was confirmed via the luciferase reporter assay and western blotting experiments, demonstrating that miR-138-1-3p can regulate the expression levels of CRIPTO. Several studies have shown that CRIPTO and GRP78 can form a complex on the cell membrane and activate the JAK2/STAT3 pathway, imparting stem cell like characteristics in the host cell with increased proliferation activity (18,31). Our immunohistochemical analysis revealed the colocalization of CRIPTO and GRP78 on the cell membrane that changed when miR-138-1-3p expression was altered.…”
Section: Discussionmentioning
confidence: 62%
“…Studies have demonstrated that, in response to tissue damage signals, MSCs release paracrine/endocrine factors that help control inflammation and stimulate tissue regeneration by endogenous mechanisms [ 55 ]. The recognition of these immunomodulatory/trophic actions with beneficial effects and migratory capacity in different tissues makes MSCs a unique therapeutic strategy [ 56 , 57 ]. These MSC characteristics have also led their original describer, Caplan, to call for a further nomenclature change to medicinal signaling cells [ 53 ].…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Blocking CRIPTO also drives dopaminergic neuron over astrocyte differentiation during neural differentiation from embryonic stem cells, thus implicating CRIPTO in control of neural stem cells and lineage fate decisions and making it an important consideration in the development of bioscaffold based stem cell transplantation approaches for neural regeneration following injury [ 81 , 82 ]. In a hindlimb ischemic model, CRIPTO was shown to interact with the concomitantly induced and overexpressed GRP78 and to synergistically increase human mesenchymal stem cell (MSC) proliferation, migration and invasion potential with potential applications for MSC-based transplantation and regeneration approaches for treating wounds [ 83 ]. There is an interesting parallel here between the hypoxic microenvironment associated with this ischemia model and the role of hypoxia in CRIPTO-mediated hematopoietic stem cell maintenance, however here as exactly how stress signals are integrated across multiple cell types has not been investigated thoroughly, and, although CRIPTO is a known Hif1 α target [ 84 ], it remains to be determined if Hif1 α is required for all adaptive responses that go through CRIPTO.…”
Section: Rise and Fall Of Criptomentioning
confidence: 99%
“…Furthermore, hypoxic conditions within these tumor regions may also influence local CRIPTO production as a function of HIF1α binding to hypoxia response elements (HREs) within the CRIPTO promoter [ 84 ]. This harkens to the integration of hypoxic stress and CRIPTO signaling in HSCs, ischemia models and cardiomyocytes [ 39 , 83 , 84 ]. Alternatively, these zones are likely starved for other nutrients and, in this regard, we found that nutrient deprivation in vitro (i.e., serum withdrawal or glycolytic blockade) confers cancer cell CRIPTO dependency [ 118 ].…”
Section: Re-emergence Of Criptomentioning
confidence: 99%